Parallel computing software technology, algorithms, architectures & applications : proceedings of the International Conference ParCo2003, Dresden, Germany, 2-5 September 2003 - ParCo2003 (Conference) (2003 : Dresden, Germany); Joubert, G. R. (Gerhard Robert) (Amsterdam : Elsevier North Holland ; Oxford : Elsevier Science, 2004)
Advances in Parallel Computing series presents the theory and use of of parallel computer systems, including vector, pipeline, array, fifth and future generation computers and neural computers. This volume features original research work, as well as accounts on practical experience with and techniques for the use of parallel computers.
Keywords: Parallel processing (Electronic computers) -- Congresses; Parallel computers -- Congresses; Parallel programming (Computer science) -- Congresses; Electronic books